ANALISIS VISUAL GAMBAR ANAK PADA MASA PRA-SKEMATIK - Nuriarta I Wayan; Dwita Krisna Ari Ida Ayu; Suryawan I Gde (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
This article aims to read visual signs and verbal signs by utilizing the children's drawings during the pre-schematic stage. The reading of the signs will be used to describe the elements of fine arts in the children's drawing. Four works of kindergarten children were chosen and observed. The four works are entitled